2018
DOI: 10.1186/s12866-018-1176-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of the tonsillar microbiome in pigs from newborn through weaning

Abstract: BackgroundPorcine tonsils are lympho-epithelial tissues, colonized by numerous bacteria and viruses, that act as a reservoir for both host-specific pathogens and zoonotic pathogens with a high potential of transmission to humans. There are no existing studies describing the development of the tonsillar microbiome. We sequenced 16S rRNA genes from tonsillar samples of pigs to follow the development of the microbial communities from birth through weaning. Samples derived from sows were also analyzed to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 48 publications
(60 reference statements)
7
57
4
Order By: Relevance
“…However, the associations were stronger in the pre-weaning phase and appeared to wane with age implying that an attempt to improve weight gain through modulation of the microbiota should target early life of the piglet, particularly before 4 weeks of life. Our findings from the taxonomic analysis of the oropharyngeal microbiota were largely in agreement with studies focusing on the tonsillar microbiota [36,42,43]. However, the dominance of Streptococcus, in our study, was striking since it was only represented as a minor community member within the tonsils [42].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the associations were stronger in the pre-weaning phase and appeared to wane with age implying that an attempt to improve weight gain through modulation of the microbiota should target early life of the piglet, particularly before 4 weeks of life. Our findings from the taxonomic analysis of the oropharyngeal microbiota were largely in agreement with studies focusing on the tonsillar microbiota [36,42,43]. However, the dominance of Streptococcus, in our study, was striking since it was only represented as a minor community member within the tonsils [42].…”
Section: Discussionsupporting
confidence: 92%
“…PCoA showed that the samples already clustered closely by day 11 of age regardless of maternal or foster sow, that nursed them. Pena Cortes et al [36] reported a litter effect in the tonsillar microbiota that disappeared by the third week. We did not observe this litter effect by the 11th day of life, probably due to the advancement in age of the piglets in our study compared to those in their study [36].…”
Section: Development Of the Oropharyngeal Microbial Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 64 samples were collected from pigs after weaning, which included samples from 16 piglets at week 4 and 8 piglets (2 per sow) at all subsequent time points (Table 1 ). In a previous study ( 16 ), we found a strong litter effect on the tonsil microbiome that disappeared by 3 weeks of age; therefore, we analyzed 4 pigs per litter initially but reduced this number to 2 pigs per litter (8 in total) for subsequent sampling times.…”
Section: Methodsmentioning
confidence: 99%
“…We recently completed a study of the composition and development of the tonsil microbiome in piglets from birth up to 4 weeks of age ( 16 ). The tonsil microbial communities initially clustered by litter, but then converged by 3 weeks of age, regardless of litter or housing.…”
Section: Introductionmentioning
confidence: 99%